A Comparative Study of Altruism in Christian and Islam (Journal of Comparative Study of Religions, 2023)
This article compares the concept of altruism in Islam and Christianity, with the specific aim of identifying their similarities and differences. The research methods employed are descriptive, comparative, and analytical within the qualitative context of literature review. Altruism itself is a philosophy that advocates the spirit of assisting others. In societal life, altruism teaches prioritizing collective interests (of others) over personal interests. When a follower of altruism is asked to help, they assist the person without discrimination. In the context of Christian teachings, altruism is at the core of Jesus' teachings found in the Gospels, particularly in the Sermon on the Mount and the Sermon on the Plain. From biblical traditions to medieval Christianity, the tension between self-affirmation and self-worth values is sometimes debated in terms of “unbiased love,” as expressed by Paul through his phrase “love seeks not its own interests.” Meanwhile, in Islam, altruism is known as īthār, meaning “preferring others over oneself.” The significance of īthār lies in the sacrifice for a greater good; in Islam, the practice of īthār is considered an action reaching the highest level of nobility.